Endoscopic dacryocystorhinostomy without mucosal flap : Our experience (Bangladesh Journal of Otorhinolaryngology, 2013)
Background: The purpose of our study was to evaluate outcome of Endoscopic dacryocystorhinostomy without preservation of mucosal flap for the management of acquired nasolacrimal duct obstruction Methods: A retrospective review of 26 patients were performed on patients who underwent Endoscopic dacryocystorhinostomy without preservation of mucosal flap from March 2007 to November 2010 at our hospital. Twenty six patients were operated and followed up postoperatively for five to six weeks with lacrimal syringing by ophthalmologists and diagnostic endoscopy done at third month and followed up until the formation of well formed ostium and patients became asymptomatic. Main outcome were subjective improvement in epiphora and persistence of anatomic patency of ostium. Result: There were 26 patients operated, one is male and all others were female. The age of patients were ranging within 20 to 78 years (mean 36.65years).Every patients were followed up in the range of four months to two years (mean 6.2 months). Septoplasty was required in only one patient prior to DCR. Anatomic patency were confirmed by nasal endoscopy in twenty four patients (92%), remaining two had synechiae without ostium. One patient among 24 patients had ostium and lacrimal flow with intermittent epiphora. Our overall success rate with anatomical patency and without symptoms of epiphora is 88%. Conclusion: Our results with endoscopic dacryocystorhinostomy are comparable with previously published outcomes. Our data suggest that endoscopic dacryocystorhinostomy without preservation of mucosal flap may be performed DOI: http://dx.doi.org/10.3329/bjo.v19i1.11728 Bangladesh J Otorhinolaryngol 2013; 19(1): 41-45